A estratégia da produção e circulação católica do projeto editorial das coleções de Theobaldo Miranda Santos: (1945-1971) - Almeida Filho, Orlando José de (2008)
The inquiry of this work turned toward the collections Curso de Psicologia e Pedagogia, Curso de Filosofia e Ciências and the volumes published in the collections Atualidades Pedagógicas and Iniciação Científica by professor Theobaldo Miranda Santos. The period between 1945 and 1971 corresponds to the time of publications of those collections. The author was also the publisher of two of the collections: Curso de Psicologia e Pedagogia and Curso de Filosofia e Ciências. He also published some volumes in the collections Atualidades Pedagógicas and Iniciação Científica directed initially by Fernando de Azevedo up to 1946 and later, by Damasco Penna. Inserted in the perspective of Cultural History, the research intends to operate with the study of the collections in its materiality in view of the strategies of the production, circulation, appropriation and imposition of the catholic model as an educational political project. The production and the edition of the collections were inserted in a context of disputes for the domain of the educational field, especially between pioneers and catholics. From the edition, production and circulation of these materials, in which the plot and disputes for the conquest of the educative place are perceived, it is also possible to understand how the knowledge propagated in the collections has constructed and prescribed pedagogical practices based on the catholic pedagogical model. From this problematic, the work searches to understand, through the material analysis of the collections, which had been the publishing and catholics strategies to conquer the market in a process of modulation of a pedagogy that brought in its volumes prescriptions of knowledge toward the formation of the professor. The collections had been part of a major project of the catholics for intervening in the culture, shaping the knowledge in the catholic perspective